2015
DOI: 10.1111/gbb.12254
|View full text |Cite
|
Sign up to set email alerts
|

Replication of ZNF804A gene variant associations with risk of heroin addiction

Abstract: Heroin addiction is heritable, but few specific genetic variants have been reproducibly associated with this disease. The zinc finger protein 804A (ZNF804A) gene is a biologically plausible susceptibility gene for heroin addiction, given its function as a transcription factor in human brain. Novel associations of two common ZNF804A single nucleotide polymorphisms (SNPs), rs7597593 and rs1344706, with heroin addiction have been reported in Han Chinese. Both SNPs have also been implicated for regulating ZNF804A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Genes encoding zinc finger proteins ( ZNF ) have also been associated with abnormal and/or criminal behavior. For example, some polymorphisms of ZNF804A gene have been associated with drug abuse in European Americans, while Tiihonen et al reported that, in the brains of violent offenders, ribosomal pseudogene RPL10P9 and ZNF132 were upregulated [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding zinc finger proteins ( ZNF ) have also been associated with abnormal and/or criminal behavior. For example, some polymorphisms of ZNF804A gene have been associated with drug abuse in European Americans, while Tiihonen et al reported that, in the brains of violent offenders, ribosomal pseudogene RPL10P9 and ZNF132 were upregulated [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our convergent analyses identified several intriguing genes in addition to those previously highlighted for ND (CHRNA5-CHRNA3-CHRNB4, CHRNB3-CHRNA6, and CHRNA4 6 ). These included genes previously associated with diseases for which cigarette smoking is a significant risk factor, such as cocaine addiction (RBFOX1), 42 alcohol dependence (THSD7B), 43 schizophrenia (ZNF804A) 44 and heroin addiction 45,46 (ZNF804A), rheumatoid arthritis (PDE2A), 47 and prostate cancer (APOL3) 48 (Table 3). Furthermore, RBFOX1 was highlighted in a recent study on the genetic relationship between schizophrenia and ND.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Polygenic risk scores based on GWAS-identified variants for schizophrenia or bipolar disorder have shown significant associations with smoking, alcohol, and substance use disorder phenotypes [123125]. Early examples of genetic variants that demonstrate such pleiotropy, i.e., exert effects on more than one outcome, across addiction and other psychiatric diseases include: ZNF804A SNP rs1344706, the first genome-wide significant finding for schizophrenia [126] and later extended to heroin addiction [127, 128]; and the BDNF SNP rs6265 and CHRNA5 SNPs rs16969968 and rs1051730 implicated at genome-wide significance for smoking (Table 1) and extended to schizophrenia/bipolar disorder outcomes [129, 130]. As the sample sizes for addiction GWAS expand to sizes comparable with other psychiatric disease GWAS, polygenic risk scores and top loci that comprise these scores are likely to reveal even more extensive sharing.…”
Section: Potential For Future Gwas To Broaden the Known Genetic Etiolmentioning
confidence: 99%